Management of Endothelial Dysfunction in Systemic Sclerosis: Current and Developing Strategies - Zanin-Silva, Djúlio César; Santana-Gonçalves, Maynara; Kawashima-Vasconcelos, Marianna Yumi; Oliveira, Maria Carolina (Frontiers in Medicine, 2021)
Systemic Sclerosis (SSc) is an autoimmune disease marked by dysregulation of the immune system, tissue fibrosis and dysfunction of the vasculature. Vascular damage, remodeling and inadequate endothelial repair are hallmarks of the disease. Since early stages of SSc, damage and apoptosis of endothelial cells (ECs) can lead to perivascular inflammation, oxidative stress and tissue hypoxia, resulting in multiple clinical manifestations. Raynaud's phenomenon, edematous puffy hands, digital ulcers, pulmonary artery hypertension, erectile dysfunction, scleroderma renal crisis and heart involvement severely affect quality of life and survival. Understanding pathogenic aspects and biomarkers that reflect endothelial damage in SSc is essential to guide therapeutic interventions. Treatment approaches described for SSc-associated vasculopathy include pharmacological options to improve blood flow and tissue perfusion and, more recently, cellular therapy to enhance endothelial repair, promote angiogenesis and heal injuries. This mini-review examines the current knowledge on cellular and molecular aspects of SSc vasculopathy, as well as established and developing therapeutic approaches for improving the vascular compartment.